2009
DOI: 10.1089/ten.tea.2008.0499
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Small-Caliber Vascular Graft Based on a Novel Biodegradable Composite Fibrin-Polylactide Scaffold

Abstract: Small-caliber vascular grafts (< or =5 mm) constructed from synthetic materials for coronary bypass or peripheral vascular repair below the knee have poor patency rates, while autologous vessels may not be available for harvesting. The present study aimed to create a completely autologous small-caliber vascular graft by utilizing a bioabsorbable, macroporous poly(L/D)lactide 96/4 [P(L/D)LA 96/4] mesh as a support scaffold system combined with an autologous fibrin cell carrier material. A novel molding device w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 40 publications
1
66
0
Order By: Relevance
“…In particular, plasma fibrinogen can polymerize to fibrin on biomaterial surfaces, and fibrin mediates a variety of cellular behaviors, including adhesion, proliferation, and migration. 26,44 In this study, we found that platelet-poor plasma significantly improved cell seeding efficiency (Fig. 4) and proliferation (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…In particular, plasma fibrinogen can polymerize to fibrin on biomaterial surfaces, and fibrin mediates a variety of cellular behaviors, including adhesion, proliferation, and migration. 26,44 In this study, we found that platelet-poor plasma significantly improved cell seeding efficiency (Fig. 4) and proliferation (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…22 As an alternative to collagen for natural ECM-based scaffolds, fibrin holds particular promise because of its ability to induce collagen and elastin synthesis and improved mechanical properties. 23 Furthermore, by combining fibrin gels with biodegradable polymeric scaffolds followed by seeding of autologous arterial-derived cells, 24 endothelialized vessels have been successfully implanted in the carotid arteries of sheep. 25 Decellularized tissue, often in the form of a xenogeneic, can serve as a naturally available scaffold.…”
Section: Extracellular Matrix-based Natural Materialsmentioning
confidence: 99%
“…commun.]. The recent work of Jockenhoevel and colleagues combines the use of fibrin gels with biodegradable scaffolds (knitted polylactide) [Tschoeke et al, 2009]. After 21 days of dynamic conditioning, these grafts seeded with ovine vascular cells had only a burst pressure of 466 8 78 mm Hg (ID ; 5 mm), which was ; 1/3 that of the ovine carotid artery.…”
Section: Cell-seeded Collagen Gelsmentioning
confidence: 99%